'Why are you carrying him? Where is the mother?': Male caregiving and the remaking of fatherhood and masculinity in Mizoram, Northeast India. Issue 4 (2nd October 2019) - Burgher, Isabela; Flood, Michael
ABSTRACT: Viewed as strategic for achieving gender equality, involved fatherhood and the relationship between caregiving and masculinity are increasingly a focus of research. Qualitative research among thirteen urban-dwelling educated men identified as 'involved' fathers in Mizoram, Northeast India explores fatherhood in a context where childcare has long been seen as the preserve of women and a discourse of 'new fatherhood' has not yet taken root. We argue that a child-oriented 'family-man' masculinity has emerged at the intersection of various recent social changes and, critically, personal reflections on the shortcomings of the currently still dominant style of fatherhood predicated on distance from childrearing and household tasks. We discuss the implications of the emergence of involved fatherhood practices among these men for locally hegemonic masculinity.